Sistem Diagnosis Penyakit Pada Tanaman Melon Menggunakan Metode Naive Bayes - Erwan Wahyu Andrianto; Nurul Hidayat; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Melon is one of the most popular fruits in Indonesia. According to experts Antok Wahyu Sektiono melon which has Latin name Cucumis Melo included in the tribe of pumpkin or Cucurbitaceae. However, in Indonesia itself, melon fodder according to the survey from the Ministry of agriculture actually has doubled from 2008 to 2013. The mentioned problems can be solved by recognizing the common symptoms of melon disease. Common symptoms have similarities with other symptoms of the disease, so the public difficulty in recognizing the common symptoms of melon disease with other diseases. The problem of recognizing the symptoms of melon disease can be solved by expert system. Expert systems apply knowledge of melon disease symptoms into the system. Android is a mobile-based operating system. Android itself has a lot of users in Indonesia. For that android-based expert system certainly can reach the wider community. The method used in this expert system is Naive Bayes. The method is implemented on expert system inference engine in order to make a conclusion based on knowledge available on the knowledge base. Results obtained after an accuracy test of 96% indicating that the method of Naive Bayes is suitable for cases of melon disease.